-2y+3+6y=11

Simple and best practice solution for -2y+3+6y=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2y+3+6y=11 equation:


Simplifying
-2y + 3 + 6y = 11

Reorder the terms:
3 + -2y + 6y = 11

Combine like terms: -2y + 6y = 4y
3 + 4y = 11

Solving
3 + 4y = 11

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 4y = 11 + -3

Combine like terms: 3 + -3 = 0
0 + 4y = 11 + -3
4y = 11 + -3

Combine like terms: 11 + -3 = 8
4y = 8

Divide each side by '4'.
y = 2

Simplifying
y = 2

See similar equations:

| 16-2n=2n+4 | | 12y+9x=15 | | 4x^2+x-2x^2+3x= | | Solvek+4-5(k+2)=3k-2 | | X-8=9.11 | | 8t+(-8)=48 | | 3(-8+x+1)+8=80 | | 8t+(-7)=48 | | 24=5x+y | | -1(-3x+2)= | | 16(-18-17d)= | | 8t+(-7)=56 | | 6+3x+.5x^2=0 | | 2x^3-18x^2-36x= | | 6(x+3)-4=4x+28 | | 3x-22=2x+13 | | 20log(x)=26 | | 3x-3y-(2x-3y)= | | 4x+y=22500 | | 2G=2 | | 9y-7=14y+3 | | x-6*5=-40 | | r=2pir | | 2*z*y^2= | | 22s=16+(15s+12) | | C-100=3 | | 310-9x=13 | | c+4=4 | | 12+5n=n-7-1 | | 25x^2-30x-7=33 | | 6t+(-8)=48 | | 4S=84 |

Equations solver categories